The Impact of Covid-19 Pandemic on Learning Implementation of Primary and Secondary School Levels - P. Ayu Suci Lestari; Gunawan Gunawan (Indonesian Publication Center, 2020)
One of the policies of the Indonesian government to break the chain of distribution of COVID-19 is to impose social distancing at all levels of society, including for learning activities at primary and secondary school levels. Schools are closed but learning activities must continue. Teachers and students are encouraged to turn to online learning. This study aims to describe the impact of the pandemic on the learning implementation at the primary and secondary school level that occurred in Indonesia. This research uses descriptive content analysis study method. The data obtained is the result of a review of various scientific articles, both national and international journals relating to the learning implementation during the pandemic. The results of the review show that online learning systems utilizing digital platforms at the elementary and secondary school levels tend to change the face of education toward better, more effective, and more enjoyable. The teacher becomes more innovative in packaging teaching materials and is more creative in developing learning methods to attract student enthusiasm. However, it needs to be adjusted again with various abilities of each teacher, student, and parent of students in providing this online learning facility, so that the constraints experienced can be minimized.